Analisa Proteksi Gangguan Petir Pada SUTT 70 KV Antara GI Kebonagung - Polehan - Priya Surya Harijanto; Budi Eko Prasetyo (Politeknik Negeri Malang, 2023)
In maintaining the continuity of its distribution, routine maintenance and a good security system are needed to anticipate abnormal conditions. This study analyzes lightning disturbances along the 70 kV transmission line from the Kebonagung substation to the Polehan substation with different strike point conditions, as well as studies the condition of the equipment when a direct strike occurs in the 70 kV transmission. From the results of the analysis when a direct strike on the phase wire of 1098 kV goes to the Kebonagung Substation, the arrester will work to throw the overvoltage to the ground, so the lightning voltage that reaches the Kebonagung Substation equipment is less than 60 kV so that the equipment at the Kebonagung Substation is protected from disturbance lightning. However, if the arrester does not work when there is a direct strike, then the damaged equipment is CVT (739.26 kV), Ds Line (545.56 kV) and CT (378.274 kV), because the BIL of the equipment is smaller than the lightning voltage that reaches and causing the system to shut down. When an indirect strike of 97.068 kV goes to the Kebonagung substation, the arrester will work and the equipment at the Kebonagung substation is protected. However, if the arrester does not work, the equipment is still protected because the CVT (65.347 kV), DS Line (16.95 kV) and CT (4.230 kV), the BIL of each equipment is higher than the incoming lightning voltage.